2022
DOI: 10.1111/jdv.18508
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of N‐acetylcysteine in trichotillomania (hair‐pulling disorder), skin‐picking disorder and onychophagia (compulsive nail‐biting)

Abstract: Dear Editor Trichotillomania (TTM), skin-picking disorder (SPD) and onychophagia are psychodermatologic conditions of primary psychiatric genesis categorized under obsessive compulsive and related disorders in the DSM-5. Due to limited efficacy of current treatments for these conditions, novel treatments, including N-acetylcysteine (NAC), are being evaluated. 1 This study comprehensively summarizes treatment outcomes of NAC for TTM, SPD and onychophagia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…For example, a recent review included a total of 19 studies (126 patients) and highlighted the use of NAC as a safe and effective treatment for patients with TTM, SPD and onychophagia. 46 This review provided a comprehensive understanding of high-level evidence regarding the pharmacological treatment options for various PPDs. Meanwhile, it is crucial for clinicians to understand the challenges of studying PPDs in RCTs and be familiar with other treatment options identified in other studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, a recent review included a total of 19 studies (126 patients) and highlighted the use of NAC as a safe and effective treatment for patients with TTM, SPD and onychophagia. 46 This review provided a comprehensive understanding of high-level evidence regarding the pharmacological treatment options for various PPDs. Meanwhile, it is crucial for clinicians to understand the challenges of studying PPDs in RCTs and be familiar with other treatment options identified in other studies.…”
Section: Discussionmentioning
confidence: 99%
“… 45 NAC indirectly elicits an inhibitory effect on synaptic release of glutamate and restoration of extracellular glutamate levels in the nucleus accumbens to improve impulse control. 46 Overall, the specific mechanisms of these pharmacological interventions for PPDs are still unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, NAC has been implicated in offering therapeutic benefits for psychiatric disorders, such as depression (Deepmala et al 2015 ). NAC also appears promising in treating trichotillomania, a hair-pulling disorder frequently associated with psychological factors (Kashetsky et al 2023 ). However, in a randomized double-blind clinical trial, it was shown that NAC did not demonstrate a statistically significant difference in the treatment of trichotillomania compared to the placebo group (Bloch et al 2013 ).…”
Section: Underlying Mechanismsmentioning
confidence: 99%
“…15 Furthermore, a recent metaanalysis investigating the use of NAC for trichotillomania, SPD, and onychophagia (compulsive nail-biting) found a range of NAC regimens-600 mg to 3000 mg daily for 0.5 to 10 monthsto be a safe and effective treatment. 16 However, a 2022 literature…”
Section: Memantinementioning
confidence: 99%